Peripheral influences on the size and organization of somatotopic representations in the fetal rat cortex - Killackey, HP (J Neurosci, 1994)
Nerve lesions at different fetal ages and on the day of birth were used to determine the role of the periphery in establishing territories devoted to representations of different portions of the body surface in rat somatosensory cortex. Transection of the infraorbital nerve (ION), the trigeminal branch that supplies the whisker pad, resulted in a significant reduction in the area within the primary somatosensory cortex devoted to the representation of the mystacial vibrissae in fetal, but not newborn, rats. Such lesions in fetal, but not neonatal, rats also resulted in significant increases in the cortical area devoted to the representation of the lower lip and jaw. There was a significant positive correlation between the reduction in the vibrissae representation and the expansion of that of the lower lip and jaw. Damage to the ION in either neonatal or fetal rats failed to increase significantly the amount of cortex devoted to the representation of the forepaw. These results indicate that the primary afferent innervation of the periphery does influence the amounts of cortex devoted to representations of different parts of the body surface and that the representation of one region can expand significantly when that of another body part is reduced.